MORAL MESSAGE IN THE FILM STAND BY ME DORAEMON 2 - Ramdhan, Nauval Ammar Triatama; Febrianty, Fenny (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
In a film, there is a moral message contained in it. Knowing the moral message contained in the film, the audience must analyze the film. Therefore, this research aims to represent the moral message of the film Stand By Me Doraemon 2. This research aims to discover what moral messages are contained in the film Stand By Me Doraemon 2. The method used in this research is qualitative analysis. The results of this research show that there are five forms of moral messages in the film Stand By Me Doraemon 2, such as not being confident, helping others, caring, loving, and keeping promises. It is hoped that this research can motivate readers and understand the contents of a film regarding the moral message contained therein.